6x-8=82-9x

Simple and best practice solution for 6x-8=82-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-8=82-9x equation:


Simplifying
6x + -8 = 82 + -9x

Reorder the terms:
-8 + 6x = 82 + -9x

Solving
-8 + 6x = 82 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-8 + 6x + 9x = 82 + -9x + 9x

Combine like terms: 6x + 9x = 15x
-8 + 15x = 82 + -9x + 9x

Combine like terms: -9x + 9x = 0
-8 + 15x = 82 + 0
-8 + 15x = 82

Add '8' to each side of the equation.
-8 + 8 + 15x = 82 + 8

Combine like terms: -8 + 8 = 0
0 + 15x = 82 + 8
15x = 82 + 8

Combine like terms: 82 + 8 = 90
15x = 90

Divide each side by '15'.
x = 6

Simplifying
x = 6

See similar equations:

| 3(x-13)(x-17)=(3x-39)(x-17) | | 7ax(12b)xc= | | x^2+y^2-10*y+25=0 | | 5h-12+5=4h-3-h | | 7x+4=3x+40 | | 6(2x-3)=2(2x+3) | | z^2-5/2iz-1=0 | | x^6+2x^4-11x^2-12=0 | | 7x+6-2x+x=18 | | 2e^(3/(3-x)) | | x*sqrt(x)-1=0 | | 6x+9=4x-14 | | 9n^2-18n-7=0 | | 5cos(2x)=5 | | p^2+4p+5=1 | | x^3-2x-3=0 | | 2*x=x+5 | | 10m-6=5m+1.5 | | 2(a+y)= | | 5i-10=3i+390 | | (2x-2)(3x-6)-(3x-6)-(3x-27)2x=0 | | 3(m-2n)-2(m-4n)= | | 4*(z+1)-7=33 | | y:6-11=9 | | 7x+8y=114 | | y=8-3*10 | | 8x=7x+56 | | X-3/5=4x/3 | | 4/11=12/x | | 1x+3y=7.50 | | 5(x+1)=3x-16 | | x^2+y^2+6x-2y+8=0 |

Equations solver categories